The effects of quality of engine oil on the CO2 emissions by motor vehicles - Kulczycki, Andrzej (Studia Ecologiae et Bioethicae, 2016)
This paper discusses the effects of engine oil on the CO2 emissions by motor vehicles. The relationship between engine lubrication and fuel consumption and CO2 emission is presented. The paper focused on the analysis of the influence of rheological properties of engine oil over a wide range of temperature and pressure on the frictional resistance of engine components. It is possible to apply the previously developed for boundary lubrication relationship to the quantitative description of changes in oil viscosity due to temperature and pressure changes. It is indicated that the use of this dependence will allow better control of the rheological properties of engine oils so as to achieve the smallest possible energy loss in terms of engine operating conditions, to overcome the frictional resistance of engine parts and consequently reduce fuel consumption and subsequent CO2 emission to atmospheric air.